Fashion and social media marketing a descriptive study of fashion advertising media in the age of Web 2.0 - Occenola, Pauline Gel C.; Sarmiento, Ma. Alicia A. (Quezon City UP College of Home Economics, 2012)
ABSTRACT From traditional media platforms, such as print and television ads, advertising has evolved to accommodate new channels. Social Media, through fashion blogs and networking platforms like Facebook, has led to a phenomenon called Social Media Marketing. This has affected how fashion is advertised, especially in the age of Web 2.0, where models of communication have changed to include user-generated content. This study generally aimed to describe the use of social media, specifically the fashion blog, for fashion advertising ; and evaluate how to best utilize this phenomenon. Specifically, the study aims to identify the criteria by which a retailer chooses the fashion blog and social media in which it would advertise. Guidelines and criteria, as well as the specific protocols for sponsorship and advertising, were identified through interviews with individual bloggers featured in this study. Purposive sampling was used in order to identify the respondents. The respondents were classified under three categories.
Thesis (BSCT)--University of the Philippines.
Keywords: Fashion merchandising -- Philippines; Advertising -- Fashion -- Philippines